THE SPECIFICITY OF THE VALUES OF SCIENTIFIC KNOWLEDGE - Skyba, Ivan (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
The article addresses the relevant issue of the specificity of the values of scientific knowledge. Two main values are considered: cognitive and instrumental. Their direct proportional interrelation and mutual conditioning are demonstrated. The significance of these values is determined by the regulative function of science, which may be directed either toward adaptation to the environment or its transformation. The aim of the article is to explore the characteristics of the values inherent in scientific knowledge. Research methods. Systematic, cultural-historical and sociocultural methodological approaches are used in their dialectical interconnection. Research results. In Antiquity, the cognitive value prevailed – science was pursued for the sake of truth, while its usefulness was viewed as secondary. During the Modern era, the instrumental value of knowledge gained prominence, especially in the works of Francis Bacon, who argued for the unity of truth and benefit. In contemporary post-nonclassical science, the dialectical interrelation between cognitive and instrumental values is recognized, alongside the increasing demand for scientists’ ethical responsibility. Discussion. Fundamental and applied research is analyzed in terms of its orientation toward the generation and implementation of the cognitive and instrumental values of scientific knowledge. Conclusions. Viewing scientific knowledge through the prism of its dual value allows for a renewed, holistic understanding of the problem of science. It is essential not to reduce it merely to usefulness but to also acknowledge the cognitive value of scientific knowledge and their dialectical interrelation. The emergence of post-nonclassical rationality in science and the growing emphasis on the moral responsibility of scientists in contemporary society to a certain extent determine the specificity of the growth and practical implementation of the cognitive and instrumental values of scientific knowledge.